IKLAN LAYANAN MASYARAKAT GO GREEN MELALUI MEDIA POSTER - Abel Azonda, Dra. Jupriani, M.Sn, Drs. Suib Awrus, M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Have you ever imagined a world filled only by men only. Many animals are extinct(except animal parasites), as well as plants. It's a very terrible situation when the rain forestturned into deserts, rivers dry up and the sources of life dwindling. Humans as the onlyruler on earth grows like ants spend all the resources present and future. Living may only former planet called